Optimization of coconut byproducts with response surface methodology (RSM) as complete nutrients on eggplant plant - Ahmad, Fandi; Sondakh, Rian Christian; Kawet, Frilly (Jurnal Agroekoteknologi Terapan, 2025)
Eggplants are good for heart health and help suppress cholesterol and diabetes. Coconut waste is a widespread environmental problem because it is not utilized correctly. Coconut waste piles up and triggers the spread of disease and becomes a habitat for mosquitoes that cause dengue fever. This study aims to improve the planting media of cocopeat, manure, and coconut fibre liquid organic fertilizer (CFLF) through a systems approach. This research method uses the response surface methodology (RSM) experimental design. The output variables from FS are converted into data sets that will be formulated in RSM. The output from the C-organic, nitrogen, phosphorus, and potassium analysis parameters is closely related (Sig <0.05) to the research factors. The RSM results show that 20 experiments will be used in the study. The cocopeat, manure, and CFLF factors only produced significant results in the potassium parameter anova test (P <0.05) with a linear statistical model with a verification test. The highest content obtained was 8.684%, nitrogen 0.752%, phosphorus 35.052 ppm, and potassium 63.216 ppm. The optimum condition was produced at 50% coconut fibre, 51.14% manure, and 50% CFLF. The results of the treatment optimization were applied to plants with an average number of fruits of 4.66 (fruits), fruit length of 20.08 (cm), diameter of 4.31 (cm), and fruit weight of 138.52 g. A practical method based on the concentration of planting media and liquid organic fertilizer is needed to increase the potential for harvest yields and promote environmental sustainability Keywords: Coconut; Feature Selection; RSM; Fertilizer; byproduct.